V-MEET Android Application - Shree, Bobby G; Ambika V; B, Divya; T, BinduMadhavi; H, Aditya Pai (International Journal of Computer Sciences and Engineering, 2025)
Android based applications are currently in trend. Several business use this android application to make their work more efficient. The applications are used in the fields like ordering food, medicine, booking tickets and also can be used to book appointment between student and lecturer which reduces their some work load. In this study presents an android application for booking appointment through mobiles where both students and lectures as to be in their respective mentioned at particular time. This application allows students and lectures to access the system by connecting through internet. It also have a feature like dropping a message which indicates the purpose of the meeting and also the student can set a time during the appointment booking. The application is developed using Java as scripting language and used My Structured Query Language (MySQL) for database. This application is cheap and capable of operating on various mobile devices and also user-friendly, very effective and efficient application which can be used by the institutions.